Respuesta :

Answer:

(x−3)(x+5) is the factorised form of the expression.

Step-by-step explanation:

x2+2x−15

We can Split the Middle Term of this expression to factorise it.

In this technique, if we have to factorise an expression like ax2+bx+c, we need to think of 2 numbers such that:

N1⋅N2=a⋅c=1⋅(−15)=−15

AND

N1+N2=b=2

After trying out a few numbers we get N1=5 and N2=−3

5⋅(−3)=−15, and 5+(−3)=2

x2+2x−15=x2+5x−3x−15

=x(x+5)−3(x+5)

=(x−3)(x+5) .

(x−3)(x+5) is the factorised form of the expression.

Tasyha

Answer:

(x - 3) and (x + 5) is the factorize form of x² + 2x - 15

Step-by-step explanation:

[tex] {x}^{2} + 2x - 15[/tex]

[tex] {x}^{2} + 5x - 3x - 15[/tex]

[tex]x \times (x + 5) - 3(x + 5)[/tex]

[tex]\boxed{\green{(x + 5)(x - 3)}}[/tex]